(3QSGdI aj JMQje GdNeQs - (3eMeO Hf YHO GdYRjR GdJejej, YdGA GdOjf GdWjH GdYQHjs
(3ChdgG (B:s
(3GdMeO ddg GdPi MQe GdNeQ UjGfI dYbhd YHGOg hHYO ajbhd gPg QSGdI TGajI ai HjGf JMQje GdNeQ hhYjO ef HGTQ TQHgG s
(3BNQgG (B:s
(3adjJCed ai CMhGd GdeJYGWjf dgG GdeOefjf dTQHgG MJi jJMbb YfOg UOb gPg GdebGdI HJMUjd GdegeGJ hGUGHI GdOYhGJ hGdMeO ddg GhdGU hGNQkG hXGgQkG hHGWfkG s
(3Cdag GdeDda dTGg Hf JjehQ dfc UGMH SeQbfO hHNGQGs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs